Degenerative Diseases of the Cervical Spine : Therapeutic Management in the Subaxial Section - König, Alexander; Spetzger, Uwe (Springer International Publishing : Imprint: Springer, 2017)
The authors present anatomical, biomechanical, and clinical basic knowledge relevant to degenerative diseases of the surgical spine and describe how to choose the approach, implant, and surgical technique in detail. Numerous figures illustrate the decision-making process and surgical techniques step-by-step. The book also contains key points about implant safety and possible complications as well as an outlook to the future of cervical spine surgery. Degenerative Diseases of the Cervical Spine is aimed at spinal surgeons (neurosurgeons and orthopaedic surgeons), physical therapists, general practitioners, and rehabilitation physicians, worldwide.
Keywords: Medicine.; General practice (Medicine).; Neurosurgery.; Orthopedics.; Otolaryngologic surgery.; Traumatology.; elektronické knihy; electronic books